Ochotona (Pika) alpina subsp. alpina Pallas 1773 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Ochotona (Pika) alpina subsp. alpina Pallas 1773 Ochotona (Pika) alpina subsp. alpina Pallas 1773, Reise Prov. Russ. Reichs, Vol. 2: 701. Type Locality: "in Alpinus, rupestribus Sibiriae". Restricted by Ognev (1940:23) to Kazakhstan, Altai Mtns, Vostocho-Kazakhstansk Obl., Tigiretskoe Range, vic. of Tigiretskoe [110 km NNW Ust-Kamenogorsk]. Not Tigiretskoe, ESE Minusinsk, Krasnoyarsk Krai, Russia. Synonyms: Ochotona (Pika) alpina subsp. ater Eversmann 1842; Ochotona (Pika) alpina subsp. nitida Hollister 1912. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Lagomorpha, pp. 185-211 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 185, DOI: 10.5281/zenodo.7316519